Technology Assessment in Japan and Europe - Moniz, AntonioOkuwada, Kumi (KIT Scientific Publishing, 2016)
The goal of technology assessment (TA) is to lend support to society and policy making by promoting understanding of the problems related to the grand sociotechnical challenges of our time, as well as to assess the available options for managing them. Researchers from Japan and Europe reflected together in this book on country-specific developments to identify the conditions that must be present to anchor TA in science, politics, and society. This book helps us to learn about different cultures.